Akkermansia muciniphila is a promising probiotic - Zhang, Ting (Microb Biotechnol, 2019)
Akkermansia muciniphila (A. muciniphila), an intestinal symbiont colonizing in the mucosal layer, is considered to be a promising candidate as probiotics. A. muciniphila is known to have an important value in improving the host metabolic functions and immune responses. Moreover, A. muciniphila may have a value in modifying cancer treatment. However, most of the current researches focus on the correlation between A. muciniphila and diseases, and little is known about the causal relationship between them. Few intervention studies on A. muciniphila are limited to animal experiments, and limited studies have explored its safety and efficacy in humans. Therefore, a critical analysis of the current knowledge in A. muciniphila will play an important foundation for it to be defined as a new beneficial microbe. This article will review the bacteriological characteristics and safety of A. muciniphila, as well as its causal relationship with metabolic disorders, immune diseases and cancer therapy.